Assessment of the new Reimbursement Act functioning between January-November 2012 and its impact on pharmacies and pharmaceutical industry and oncological treatment - Winiarska, Małgorzata; Matosiuk, Dariusz (Polish Journal of Public Health, 2016)
Introduction. The new Reimbursement Act introduced on 01.01.2012 aimed at improving the way the Polish healthcare system operates, as well as reducing and unifying the prices of medicinal products. The Act provides that the prices for reimbursed drugs are lowered and unified. Increase the transparency, increase the number of innovative reimbursed drugs and lowering the level of co-payments. Aim. The authors analyze the influence of the new Reimbursement Act (introduced on 01.01.2012) over the way the Polish healthcare system works. Material and methods. The contents of the Reimbursement Act (introduced 01.01.2012) were used as research material. A content analysis of the new Act (conducted between 2013 and 2014) and its impact over the pharmaceutical industry, drug wholesale and drugstores was analyzed. Results. Some numerical data concerning retail margins, co-payments by patients, limit groups, reimbursed drug prices were showed in the study. Conclusions. Unfortunately, the Act itself has many shortcomings, inconsistencies or vague entries that require urgent amendment. Hence, it had a totally different impact.